Overtube-assisted enteroscopy and capsule endoscopy for the diagnosis of small-bowel polyps and tumors: a systematic review and meta-analysis - Sulbaran, Marianny; de Moura, Eduardo; Bernardo, Wanderley; Morais, Cintia; Oliveira, Joel; Bustamante-Lopez, Leonardo; Sakai, Paulo; Mönkemüller, Klaus; Safatle-Ribeiro, Adriana (Endoscopy International Open, 2016)
Background and study aims: Several studies have evaluated the utility of double-balloon enteroscopy (DBE) and capsule endoscopy (CE) for patients with small-bowel disease showing inconsistent results. The aim of this study was to determine the sensitivity and specificity of overtube-assisted enteroscopy (OAE) as well as the diagnostic concordance between OAE and CE for small-bowel polyps and tumors.Patients and methods: We conducted a systematic review and meta-analysis of studies in which the results of OAE were compared with the results of CE for the evaluation of small-bowel polyps and tumors. When data for surgically resected lesions were available, the histopathological results of OAE and surgical specimens were compared. The sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio for the diagnosis of small-bowel polyps and tumors were analyzed. Secondarily, the rates of diagnostic concordance and discordance between OAE and CE were calculated.Results: There were 15 full-length studies with a total of 821 patients that met the inclusion criteria. The pooled sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio were as follows: 0.89 (95 % confidence interval [CI] 0.84 – 0.93), with heterogeneity χ2 = 41.23 (P = 0.0002) and inconsistency (I2) = 66.0 %; 0.97 (95 %CI 0.95 – 0.98), with heterogeneity χ2 = 45.27 (P = 0.07) and inconsistency (I2) = 69.1 %; 16.61 (95 %CI 3.74 – 73.82), with heterogeneity Cochrane’s Q = 225.19 (P < 0.01) and inconsistency (I2) = 93.8 %; and 0.14 (95 %CI 0.05 – 0.35), with heterogeneity Cochrane’s Q = 81.01 (P < .01) and inconsistency (I2) = 82.7 %, respectively. A summary receiver operating characteristic curve (SROC) curve was constructed, and the area under the curve (AUC) was 0.97.Conclusion: OAE is an accurate test for the detection of small-bowel polyps and tumors. OAE and CE have a high diagnostic concordance rate for small-bowel polyps and tumors.This study was registered in the PROSPERO international database (www.crd.york.ac.uk/prospero/) with the study number CRD42015016000.